2004
DOI: 10.1207/s15327604jaws0701_1
|View full text |Cite
|
Sign up to set email alerts
|

Employee Reactions and Adjustment to Euthanasia-Related Work: Identifying Turning-Point Events Through Retrospective Narratives

Abstract: This study used a retrospective narrative procedure to examine the critical events that influence reactions and adjustment to euthanasia-related work of 35 employees who have stayed in the animal care and welfare field for at least 2 years. The study analyzed adjustment trajectory graphs and interview notes to identify turning-point events that spurred either a positive or negative change in shelter workers' psychological well-being. Analysis of the identified turning-point events revealed 10 common event them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(85 citation statements)
references
References 43 publications
1
66
2
Order By: Relevance
“…Congruent results were identified between this study and previous research which found that euthanasia typically has a negative impact on an individual's health and well-being (Arluke 1991, White and Shawhan 1996, Stamm 1997, Reeve, Spitzmuller et al 2004, Reeve, Rogelberg et al 2005, Rohlf and Bennett 2005. With a survey instrument devised by the researchers, this particular cross-sectional study (Rogelberg, Reeve et al 2007) found a significant correlation between euthanasia rates and employee turnover index (r = 0.36, P < 0.05) that is, higher euthanasia rates were associated with increased employee turnover.…”
Section: Quantitative Studiescontrasting
confidence: 61%
See 4 more Smart Citations
“…Congruent results were identified between this study and previous research which found that euthanasia typically has a negative impact on an individual's health and well-being (Arluke 1991, White and Shawhan 1996, Stamm 1997, Reeve, Spitzmuller et al 2004, Reeve, Rogelberg et al 2005, Rohlf and Bennett 2005. With a survey instrument devised by the researchers, this particular cross-sectional study (Rogelberg, Reeve et al 2007) found a significant correlation between euthanasia rates and employee turnover index (r = 0.36, P < 0.05) that is, higher euthanasia rates were associated with increased employee turnover.…”
Section: Quantitative Studiescontrasting
confidence: 61%
“…Included throughout this thesis are comments and statements that the researcher found particularly poignant and important to emphasise to the audience of this work; these are presented in boxes at the beginning or end of each Chapter. The themes identified in Chapter 4 recur in other Chapters of this thesis as well as being generally present in existing knowledge (Arluke 1991, White and Shawhan 1996, Reeve, Spitzmuller et al 2004, Reeve, Rogelberg et al 2005, Rohlf and Bennett 2005, Rogelberg, DiGiacomo et al 2007, Baran, Allen et al 2009, Baran, Rogelberg et al 2012). …”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations